Penerapan Promosi Kesehatan Metode Brainstorming Terhadap Pengetahuan Klien Tentang Tanda-Tanda Bahaya Kehamilan: Application of Health Promotion Brainstorming Method to Pregnant Women's Knowledge About Danger Signs of Pregnancy - Sri Wahyuni; Sri Maryati (Journal of Health, 2024)
One indicator that can show the well-being of a country's population is the number of maternal and infant deaths. Hemorrhage, hypertension during pregnancy, and diseases of the circulatory system are the leading causes of maternal mortality. One of the factors that contribute to a mother's ability to identify early signs of pregnancy danger and conduct early treatment is her knowledge. One way to encourage health promotion is to use an appropriate method, namely brainstorming. This study aims to improve the knowledge of pregnant women about the danger signs of pregnancy before and after receiving health promotion through the Brain Storming method. In this study, researchers used a pre-experimental design with a one group pretest postest design. This study involved pregnant women consisting of 30 people to undergo pregnancy checks in the Cipeundeuy Health Center area through purposive sampling method. In collecting data, author used a questionnaire which was used to ask what pregnant women knew about danger signs that might occur during pregnancy. The marginal homogeneity test was used to analyze the data. The results showed that the brainstorming method was effective for improving the knowledge of pregnant women, with a p-value: 0.000 (p < 0.05). Brainstorming can increase maternal knowledge because in its implementation the client participates in expressing opinions and experiences. Therefore, health centers can use the brainstorming method to improve clients' knowledge about danger signs during pregnancy to prevent complications.